2004
DOI: 10.5194/angeo-22-289-2004
|View full text |Cite
|
Sign up to set email alerts
|

A study of Pc-5 ULF oscillations

Abstract: Abstract.A study of Pc-5 magnetic pulsations using data from the Combined Release and Radiation Effects Satellite (CRRES) was carried out. Three-component dynamic magnetic field spectrograms have been used to survey ULF pulsation activity for the approximate fourteen month lifetime of CRRES. Two-hour panels of dynamic spectra were examined to find events which fall into two basic categories: 1) toroidal modes (fundamental and harmonic resonances) and 2) poloidal modes, which include compressional oscillations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
86
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 40 publications
9
86
0
Order By: Relevance
“…A1b, when it was already at higher L. Both spacecraft see approximately the same peak frequency 3.3 mHz by 22:01 UT, with power significantly lower at spacecraft B at that time and reduced further as it passes by 22:16 UT and moves further duskward. Figure 5 shows that the mHz ULF wave PSD attenuates away from the dayside, particularly clear for spacecraft B in panel (d), which has moved more duskward than A, as has been seen in many studies, with concentration of toroidal-mode power along the flanks of the magnetosphere and compressional in B (poloidal E φ ) power across the dayside; see, for example, Anderson et al (1992a, b) for a review of AMPTE CCE magnetometer measurements, Lessard et al (1999) for analysis of the local time distribution of AMPTE IRM magnetometer data, Hudson et al (2004) for CRRES magnetometer, Liu et al (2009) for THEMIS data, and Engebretson et al (1998) for ground magnetometer studies. Other LFM CME-shock event studies (Elkington et al, 2002 have confirmed the predominance of wave power on the dayside in the poloidal E φ component and discussed the need to include that longitudinal asymmetry in any prescribed ULF wave model of effects on radial transport and acceleration of electrons.…”
Section: October 2013mentioning
confidence: 99%
“…A1b, when it was already at higher L. Both spacecraft see approximately the same peak frequency 3.3 mHz by 22:01 UT, with power significantly lower at spacecraft B at that time and reduced further as it passes by 22:16 UT and moves further duskward. Figure 5 shows that the mHz ULF wave PSD attenuates away from the dayside, particularly clear for spacecraft B in panel (d), which has moved more duskward than A, as has been seen in many studies, with concentration of toroidal-mode power along the flanks of the magnetosphere and compressional in B (poloidal E φ ) power across the dayside; see, for example, Anderson et al (1992a, b) for a review of AMPTE CCE magnetometer measurements, Lessard et al (1999) for analysis of the local time distribution of AMPTE IRM magnetometer data, Hudson et al (2004) for CRRES magnetometer, Liu et al (2009) for THEMIS data, and Engebretson et al (1998) for ground magnetometer studies. Other LFM CME-shock event studies (Elkington et al, 2002 have confirmed the predominance of wave power on the dayside in the poloidal E φ component and discussed the need to include that longitudinal asymmetry in any prescribed ULF wave model of effects on radial transport and acceleration of electrons.…”
Section: October 2013mentioning
confidence: 99%
“…Similarly to the definition used by Hudson et al [2004], here we characterize as narrowband Pc5 pulsations all magnetospheric oscillations with Df < 2 mHz at a given time, where bandwidth Df is the full width at half maximum. Such pulsations can be attributed either to the solar wind, acting as an external driver, or to internal plasma anisotropies, and are characterized by their azimuthal wave number, m [Dungey, 1954;Green, 1976], which is often indicative of the excitation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…These results have been confirmed by statistical analysis of GOES magnetic field data at geosynchronous orbit . Although excitation of ULF Pc4-5 waves has been traditionally attributed to the K-H instability, waves generated by this instability show minimum activity around noon near the subsolar stagnation region compared with the dawn and dusk sector (e.g., Anderson et al 1990;Zhu and Kivelson 1991;Lessard et al 1999;Hudson et al 2004;Takahashi and Ukhorsky 2007). The observations reported here, on the other hand, show that poloidal ULF waves associated with solar wind dynamic pressure pulses exhibit a maximum at local noon.…”
Section: Introductionmentioning
confidence: 99%
“…Sudden density or velocity increases in the solar wind produced by IP shocks lead to a step-like enhancement of the solar wind dynamic pressure and a sudden compression of Earth's dayside magnetosphere. The resulting magnetosonic waves launched into the magnetosphere (Wilken et al 1982;Kepko and Spence 2003;Hudson et al 2004;Claudepierre et al 2009) excite FLRs around magnetic local noon (Zong et al 2009a, b;) and interact with charged particles. Fig.…”
Section: Introductionmentioning
confidence: 99%